PEMBERDAYAAN PETERNAK MELALUI PELATIHAN PEMBUATAN PAKAN SILASE DIKAMPUNG YASA MULYA DISTRIK TANAH MIRING KABUPATEN MERAUKE PAPUA SELATAN - Praptiwi, Irine Ike; Rizal, Abdul; Adrianus, Adrianus; Nurcholis, Nurcholis; Yusuf, Mani; Anwar, Anwar; Malesi, Wa Ode Asriyanti Wida (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2024)
Making silage feed in Yasa Mulya Village involves 30 farmers participating in a structured training program to increase their knowledge and skills in producing quality feed. The methods applied include initial preparation and planning, opening of training sessions, delivery of theoretical material, direct practice, group discussions, and evaluation of results. In the opening session, farmers were introduced to the importance of silage as nutritious animal feed, followed by material on grass-cutting techniques, EM4 mixing, and effective storage processes. Hands-on practice provides real experience in making silage, while discussions allow exchanging ideas and solutions to the challenges faced. Through evaluation, participants can assess their understanding and formulate necessary follow-up actions for the application of the techniques learned. It is hoped that the results of this training can increase livestock productivity and support the sustainability of livestock businesses in Yasa Mulya Village